PENGARUH KENYAMANAN DAN KEMUDAHAN PENGGUNAAN FASILITAS ATM BNI TAPLUS TERHADAP KEPUASAN NASABAH PADA BANK NEGARA INDONESIA KANTOR CABANG UTAMA MAKASSAR - Dirwan Dirwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
Quantitative research is conducted to mengehui partial influence of convenience and ease of use of ATM facilities BNI Taplus to customer satisfaction Bank BNI Makassar Branch Office. Primary data in the form of questionnaire, distributed to one hundred customers in Bank BNI Makassar Branch Office. Research data were then analyzed using multiple linear regression analysis technique. Previously, the primary data were tested instruments and qualified regression analysis ie the classical assumption test. Based on the results of regression analysis and t-statistical test, this study concludes: convenience has a positive and significant impact on customer satisfaction, the first hypothesis accepted; ease of negative and significant impact on customer satisfaction; furthermore convenience has a more dominant influence than ease in customer satisfaction.